2017
DOI: 10.1007/s00520-017-3904-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized control trial of benzydamine HCl versus sodium bicarbonate for prophylaxis of concurrent chemoradiation-induced oral mucositis

Abstract: For patients undergoing high-dose radiotherapy concurrently with platinum-based chemotherapy, using benzydamine HCl mouthwash as a preventive approach was superior to basic oral care using sodium bicarbonate mouthwash in terms of reducing the severity of oral mucositis and encouraging trend for the less need of oral antifungal drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 25 publications
2
27
0
1
Order By: Relevance
“…They found no statistically significant difference between the groups receiving CRT. The second study [12] did not find a statistically significant difference between the groups. Only one study [12] recorded adverse events (AEs) and found that 6.75% of participants in the BHM group were unable to tolerate the full strength of BHM due to a burning sensation in the mouth.…”
Section: Synthesis Of Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…They found no statistically significant difference between the groups receiving CRT. The second study [12] did not find a statistically significant difference between the groups. Only one study [12] recorded adverse events (AEs) and found that 6.75% of participants in the BHM group were unable to tolerate the full strength of BHM due to a burning sensation in the mouth.…”
Section: Synthesis Of Resultsmentioning
confidence: 78%
“…Secondary outcome measures Three studies measured treatment interruptions; one study [10] found statistically significantly fewer treatment interruptions in the BHM group receiving RT alone but not in the group receiving chemoradiotherapy (CRT). One study [11] found fewer treatment interruptions but did not calculate statistical significance, and one study [12] found no statistically significant difference between the groups. Two studies measured the number of participants who required feeding tubes fitted.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…242 The NSAID benzydamine also has some data supporting its use in an oral rinse for the prevention and treatment of mucositis. 249,250 Local anesthetics (eg, lidocaine) may be used to treat mucositis either as component of a mouth rinse or separately, in a liquid or gel formulation.…”
Section: Management Of Bone Pain Without An Oncologic Emergencymentioning
confidence: 99%
“…It is capable of local anaesthetic effects by inhibiting the release of inflammatory mediators like substance P and calcitonic generelated peptide (CGRP) from sensory nerve endings. Benzydamine mouthrinse has been trialed in multiple studies assessing its effectiveness in OM, although many studies have focused on prevention of OM rather than its effectiveness on pain control (Apaydin, Karadeniz, Ayisigi, & Bilge, 1996;Chitapanarux et al, 2018;Epstein & Stevenson-Moore, 1986;Epstein et al, 2001;Jayachandran & Balaji, 2012;Samaranayake et al, 1988). Benzydamine reduced pain severity in radiotherapy patients during the early stages of cancer treatment (Kim et al, 1986).…”
Section: Discussionmentioning
confidence: 99%